Training loads, wellness and performance before and during tapering for a water-polo tournament - Botonis, P. G.; Toubekis, A. G.; Platanou, T. I. (Journal of Human Kinetics, 2019)
We investigated the effectiveness of a short-duration training period including an overloaded (weeks 1 and 2) and a reduced training load period (weeks 3 and 4) on wellness, swimming performance and a perceived internal training load in eight high-level water-polo players preparing for play-offs. The internal training load was estimated daily using the rating of perceived exertion (RPE) and session duration (session-RPE). Perceived ratings of wellness (fatigue, muscle soreness, sleep quality, stress level and mood) were assessed daily. Swimming performance was evaluated through 400-m and 20-m tests performed before (baseline) and after the end of weeks 2 and 4. In weeks 3 and 4, the internal training load was reduced by 19.0 ± 3.8 and 36.0 ± 4.7%, respectively, compared to week 1 (p = 0.00). Wellness was improved in week 4 (20.4 ± 2.8 AU) compared to week 1 and week 2 by 16.0 ± 2.2 and 17.3 ± 2.9 AU, respectively (p =0.001). At the end of week 4, swimming performance at 400-m and 20-m tests (299.0 ± 10.2 and 10.2 ± 0.3 s) was improved compared to baseline values (301.4 ± 10.9 and 10.4 ± 0.4 s, p < 0.05) and the overloading training period (week 2; 302.9 ± 9.0 and 10.4 ± 0.4 s, p < 0.05). High correlations were observed between the percentage reduction of the internal training load from week 4 to week 1 (-25.3 ± 5.5%) and the respective changes in 20-m time (-2.1 ± 2.2%, r = 0.88, p < 0.01), fatigue perception (39.6 ± 27.1%), muscle soreness (32.5 ± 26.6%), stress levels (25.6 ± 15.1%) and the overall wellness scores (28.6 ± 21.9%, r = 0.74-0.79, p < 0.05). The reduction of the internal training load improved the overall perceived wellness and swimming performance of players. The aforementioned periodization approach may be an effective training strategy in the lead-up to play-off tournaments.